AGAMA DAN KEPERCAYAAN MINORITAS SUKU ANAK DALAM (SAD) JAMBI - Setyabudi, Muhammad Nur Prabowo (Masyarakat Indonesia, 2021)
The life of the Anak Dalam tribe in Jambi province of Sumatra island is closely tied with the forest. However, the destruction of basic ecological infrastructure currently threatens the existence of other superstructures; Not only threatens the existence of indigenous communities, but also their beliefs. So far, the belief system of the Anak Dalam tribe is closely tied to the ecological system. The destruction of the forest means destruction of the way of life, system, and belief traditions of the Anak Dalam tribe that has been existed for centuries. With their belief system, the Anak Dalam tribe eventually become the most vulnerable minority in Indonesia, who always experience a dilemmatic position in front of the religion and culture of the non-SAD superior majority. Recognition of local religions in Indonesia should be a starting point to resolve the dilemma of the Anak Dalam tribe minority. The "non-religious" stigma attached to them as a minority is also unacceptable, because they have a belief system in the form of ancestral beliefs that have been recognized in the politics of religion in Indonesia. A change is needed towards a more tolerant attitude and fairer policies, and respecting religious freedom for the Anak Dalam minority group with the whole different religious and cultural characteristics.